Inequities in global access to water and sanitation. A multiscalar approach - Saurí Pujol, David; Ribas Palom, Anna (Documents d’Anàlisi Geogràfica, 2022)
The aim of this article is to reflect on the inequalities that exist between the Global North and the Global South in terms of access to water and sanitation, particularly concerning safety, reliability, and affordability. In 2010, the United Nations declared access to water and sanitation a human right. Later, in 2015, this was made one of the 17 Sustainable Development Goals (SDGs) to ensure universal and equitable access to water and sanitation services by 2030. Today, however, there has been little improvement in equality between poor and rich countries, between urban and rural areas, and between the formal city and the informal city. Achieving goal 6 of the SDGs of the UN inevitably involves reducing social and territorial inequalities, especially in the major cities of the Global South.